2016
DOI: 10.1111/ceo.12846
|View full text |Cite
|
Sign up to set email alerts
|

Survey of glaucoma surgical preferences and post‐operative care in the United Kingdom

Abstract: Background: To evaluate the spectrum of glaucoma surgery and the post-operative follow-up regimes undertaken among glaucoma specialists in the United Kingdom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…As a result, many glaucoma specialists remain unclear on what benefits and risks Xen surgery offers to their patients. In a survey of glaucoma specialists in the United Kingdom and Ireland published in 2017, less than one in five were undertaking this procedure [14].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, many glaucoma specialists remain unclear on what benefits and risks Xen surgery offers to their patients. In a survey of glaucoma specialists in the United Kingdom and Ireland published in 2017, less than one in five were undertaking this procedure [14].…”
Section: Introductionmentioning
confidence: 99%
“…Our results show a decrease of IOP and a reduction of glaucoma medications after MIGS surgery with a low complication rate. The reduced operating time and less frequent follow up and low complication rate compared to trabeculectomy may avoid the need for trabeculectomy in many patients who do not require a very low IOP 27 . This may prove cost effective and these procedures may help health care providers cope with an ever-increasing demand due to an aging population.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that the GDD had a higher or similar success rate and fewer complications [ 2 , 3 ]. For these reasons, the use of GDD has increased dramatically in the USA and UK [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%